Comparative analysis of features professional employees sensorineural hearing loss in a variety of sectors - E. E. Adeninskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The article presents comparative analysis of the results of complex long-term examination of occupational male patients of three types of economic activity: civil aviation, engineering and coal mining industry with determined diagnosis of sensorineural hearing loss.